Optimalisasi Ketepatan Membaca Al-Qur’an dengan Metode Yanbu’a di TPQ Nurul Ummah Kepuharjo Malang - Sebtia Rizki Nur Afni; Diah Handayani (Abdimas Indonesian Journal, 2022)
Inaccurate pronunciation in reading of the Holy Qur’an based on tajwid and makhorijul hurf aspects at TPQ Nurul Ummah Kepuharjo Kasembon, Malang, the background from the research with solution the Yanbu’a implementation methods. The purpose of providing assistance to learning the Holy Qur’an with the yanbua methods is an attempt to increase the accuracy of its pronunciation easier reading the Holy Qur’an at TPQ Nurul Ummah Kasembon, Malang. The Yanbu’a method is a method of learning the Holy Qur’an by reading, writing, and memorizing which is systematically arranged in seven volumes, and how to read it quickly, precisely, without spelling, directly, and not intermittently adjusted to tajwid and makhorijul hurf letter. The implementation of the Yanbu’a method in the learning of The Holy Qur’an is attemped to be one solution in increasing the accuracy of the pronunciation of reading the Holy Qur’an at TPQ Nurul Ummah Kepuharjo Kasembon, Malang. Along with this, as an effort to apply the knowledge that has been late for the community, it is also to broaden insight and experience regarding the real needs and problems faced by the community. The research method use is Asset Based Community Development (ABCD). This ABCD method to develop exiting assets, potentials, or opportunities to be more organized. The method used in the ABCD approach is Appreciative Inquiry. Like developing assets, namely TPQ Nurul Ummah from the aspect of variations of Al Qur’an learning methods and developing class structure management. The researcher suggests that this activity should continue to be programmed on an ongoing basis, in order to maintain the quality of service and gradually help in improving the quality of Islamic religious education, one of which is learning the Qur'an. The results of the study, it was concluded, (a) increasing the accuracy of pronunciation in reading the Holy Qur'an, (b) increasing the enthusiasm for learning the Holy Qur’an from the students, (c) increasing the variety of appropriate Al-Qur'an learning methods.